The anti-cancer efficacy of a novel phenothiazine derivative is independent of dopamine and serotonin receptor inhibition - Vanneste, Marion; Venzke, Anita; Guin, Soumitra; Fuller, Andrew J.; Jezewski, Andrew J.; Beattie, Sarah R.; Krysan, Damian J.; Meyers, Marvin J.; Henry, Michael D. (Frontiers in Oncology, 2023)
An attractive, yet unrealized, goal in cancer therapy is repurposing psychiatric drugs that can readily penetrate the blood-brain barrier for the treatment of primary brain tumors and brain metastases. Phenothiazines (PTZs) have demonstrated anti-cancer properties through a variety of mechanisms. However, it remains unclear whether these effects are entirely separate from their activity as dopamine and serotonin receptor (DR/5-HTR) antagonists. In this study, we evaluated the anti-cancer efficacy of a novel PTZ analog, CWHM-974, that was shown to be 100-1000-fold less potent against DR/5-HTR than its analog fluphenazine (FLU). CWHM-974 was more potent than FLU against a panel of cancer cell lines, thus clearly demonstrating that its anti-cancer effects were independent of DR/5-HTR signaling. Our results further suggested that calmodulin (CaM) binding may be necessary, but not sufficient, to explain the anti-cancer effects of CWHM-974.While both FLU and CWHM-974 induced apoptosis, they induced distinct effects on the cell cycle (G0/G1 and mitotic arrest respectively) suggesting that they may have differential effects on CaMbinding proteins involved in cell cycle regulation. Altogether, our findings indicated that the anticancer efficacy of the CWHM-974 is separable from DR/5-HTR antagonism. Thus, reducing the toxicity associated with phenothiazines related to DR/5-HTR antagonism may improve the potential to repurpose this class of drugs to treat brain tumors and/or brain metastasis.